Other Orphan Diseases 2018
DOI: 10.1136/annrheumdis-2018-eular.6004
|View full text |Cite
|
Sign up to set email alerts
|

AB1147 Evolutionary study of 45 cases of undifferentiated negative hla b27 seronegative oligoarthritis

Abstract: BackgroundThe prognosis of patients with undifferentiated arthritis may vary from self-limited to severe destructive rheumatoid arthritis. Early diagnosis is important, specially in seronegative oligoarthritis in order to start a treatment as early as possible.ObjectivesTo describe the evolution of patients older than 16 years diagnosed with negative HLA B27 seronegative oligoarthritis without axial involvement.MethodsWe retrospectively studied 45 patients (23 women, 22 men) with negative HLA B27 seronegative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 34 Furthermore, the authors found that UA later developing PsA, when compared with UA later developing rheumatoid arthritis (RA), had more mono-oligoarthritis and the articular disease was more localised and intermittent. In Exposito-Perez et al, 36 peripheral involvement was present in all new PsA diagnosis. Regarding imaging at PsA onset, data were derived only in one study, Paalaneen et al (PsA cases, n=46) in which juxta-articular new bone formation were found in 20% and pencil in cup deformities in 5%.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“… 34 Furthermore, the authors found that UA later developing PsA, when compared with UA later developing rheumatoid arthritis (RA), had more mono-oligoarthritis and the articular disease was more localised and intermittent. In Exposito-Perez et al, 36 peripheral involvement was present in all new PsA diagnosis. Regarding imaging at PsA onset, data were derived only in one study, Paalaneen et al (PsA cases, n=46) in which juxta-articular new bone formation were found in 20% and pencil in cup deformities in 5%.…”
Section: Resultsmentioning
confidence: 88%
“…Regarding UA/PsA transition, of 7873 references focusing on UA to PsA, 3 studies were included of which 1 was a retrospective cohort study, 1 a case-control study and 1 in abstract form. [34][35][36] The PRISMA flow chart is shown in figure 2. The breakdown presentation of the included studies is available in online supplemental file 2.…”
Section: Resultsmentioning
confidence: 99%